Mekanisme Trasmisi Kebijakan Moneter Ganda Jalur Harga Aset Terhadap Inflasi di Indonesia - Dini Anggreini Khairunnisa; Sofyan Rizal (Tauhidinomics: Journal of Islamic Banking and Economics, 2022)
The effectiveness of the monetary policy transmission mechanism is important to determine how strong and the lag lenght in the transmission channel. Indonesia implements a dual monetary system policy (conventional and sharia). This study aims to analyze, which monetary system has more effectiveness in controlling inflation in by using the monetary policy transmission of the asset price channel. This study uses the VAR-VECM method to see the level of speed or time lag between the two monetary systems. The results of the study show that the transmission channel of the Islamic monetary mechanism (through the asset price channel has a better effect mechanism in influencing inflation compared to the conventional monetary transmission mechanism.